Clinical predictors of survival in patients with relapsed/refractory small-cell lung cancer treated with checkpoint inhibitors: a German multicentric real-world analysis. (May 2022) - Stratmann, Jan A.; Timalsina, Radha; Atmaca, Akin; Rosery, Vivian; Frost, Nikolaj; Alt, Jürgen; Waller, Cornelius F.; Reinmuth, Niels; Rohde, Gernot; Saalfeld, Felix C.; von Rose, Aaron Becker; Acker, Fabian; et al.
Objectives: Small-cell lung cancer (SCLC) is a lung malignancy with high relapse rates and poor survival outcomes. Treatment-resistant disease relapse occurs frequently and effective salvage therapies are urgently needed. Materials and Methods: We aimed to define efficacy and safety of checkpoint inhibitors (CPIs) in a heterogeneous population of relapsed and refractory SCLC patients in a large retrospective multicentric real-world cohort across German tertiary care centers. Results: A total of 111 patients from 11 treatment centers were included. Median age of all patients was 64 years, and 63% were male. Approximately one-third of all patients had poor performance status [Eastern Cooperative Oncology Group (ECOG) ⩾ 2], and 37% had known brain metastases. Patients were heavily pretreated with a median number of prior therapy lines of 2 (range, 1–8). Median follow-up of the entire cohort was 21.7 months. Nivolumab and Nivolumab/Ipilimumab were the most common regimens. Overall disease control rate was 27.2% in all patients and was numerically higher in CPI combination regimens compared with single-agent CPI (31.8% versus 23.8%; p = 0.16). Median overall survival (OS) was 5.8 months [95% confidence interval (CI), 1.7–9.9 months]. The 12- and 24-month survival rates were 31.8% and 12.7%, respectively. The 12-week death rate was 27.9%. Disease control and response rate were significantly lower in patients with liver metastases. Platinum sensitivity (to first-line treatment), metastatic burden, and lactate dehydrogenase (LDH) showed prognostic impact on survival in univariate analysis. Neutrophil-to-lymphocyte ratio (NLR) was a significant and independent predictor of survival in univariate ( p = 0.01) and multivariate analyses [hazard ratio (HR), 2.1; 95% CI = 1.1–4.1; p = 0.03]. Conclusion: CPI in patients with relapsed or refractory (R/R) SCLC is of limited value in an overall patient cohort; however, long-term survival, in particular with CPI combination strategies, is possible. Clinical characteristics allow a more differentiated subgroup selection, in particular patients with low NLR showed less benefit from CPI in R/R SCLC.